Teacher Competency In Chinese Independent High Schools In Penang - Thong, Chean Wah (2018)
This study aimed to explore the competencies of mathematics teachers in Chinese Independent High Schools (CIHSs) of Penang state. The COACTIV model that including content knowledge (CK), pedagogical content knowledge (PCK), pedagogical/psychological knowledge (PPK), organizational knowledge, and counseling knowledge was used as conceptual framework. A total of 55 participants were selected to involve in in-depth and focus group interviews using multi-stage sampling technique. There were five groups of participants, namely five principals, five senior assistants, five mathematics department heads, 13 mathematics teachers, and 27 students of the five CIHSs. Principals, senior assistant, and mathematics department heads were involved in in-depth interviews while mathematics teachers and students were involved in focus group interviews. Results revealed that CK, PCK, and PPK are generally recognized as important to be possessed by mathematics teachers in CIHSs. However, the organizational knowledge and counseling knowledge seemed to be neglected. Findings revealed that all the five competencies, namely CK, PCK, PPK, organizational knowledge, and counseling knowledge not only fits conceptually into COACTIV model but also reinforced the theories used in this study. Finally, this study has successfully contributed to human resource management and development particularly in CIHSs and also in the field of education generally.